Recent advances in banana (Musa spp.) biofortification to alleviate vitamin A deficiency - Amah, D.; Biljon, A. van; Brown, A.; Perkins-Veazie, P.; Swennen, Rony L.; Labuschagne, Maryke T. (Informa UK Limited, 2018)
Vitamin A deficiency (VAD) is one of the most prevalent micronutrient deficiencies that disproportionately affects low income populations in developing countries. Traditional breeding and modern biotechnology have significant potential to enhance micronutrient bioavailability in crops through biofortification. Bananas (Musa spp.) are economically important fruit crops grown throughout tropical and sub-tropical regions of the world where VAD is most prevalent. Some banana genotypes are rich in provitamin A carotenoids (pVACs), providing an opportunity to use bananas as a readily available vehicle for provitamin A delivery. This review summarizes the progress made in carotenoid research in bananas relative to banana diversity and the use of conventional breeding and transgenic approaches aimed at banana biofortification to address vitamin A deficiency. Existing reports on sampling strategies, pVAC retention and bioavailability are also evaluated as essential components for a successful banana biofortification effort. The wide variability of pVACs reported in banana cultivars coupled with recent advances in unravelling the diversity and genetic improvement of this globally important but often-neglected staple fruit crop underscores their importance in biofortification schemes.